1995
DOI: 10.1029/95wr00518
|View full text |Cite
|
Sign up to set email alerts
|

Similarity in Catchment Response: 1. Stationary Rainstorms

Abstract: The variability in Hortonian surface runoff discharge and volume produced by stationary rainstorms on watersheds with spatially distributed soil saturated hydraulic conductivity is examined using a two-dimensional runoff model and a Monte Carlo methodology. Results indicate that rainfall duration tr, rainfall intensity i, representative time to equilibrium tre, mean saturated hydraulic conductivity Kin, and coefficient of variation C v play major roles in the variability of surface 'runoff. Similarity in surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 19 publications
4
45
1
Order By: Relevance
“…[32] Several authors noted that q 5 1 is a critical value in the Monte-Carlo simulation of hillslopes or catchments [Saghafian et al, 1995;Nahar et al, 2004;Morbidelli et al, 2006;Jones et al, 2009]. The case of a periodic variation of infiltrability best illustrates the transition at q 5 1.…”
Section: Fðyþgðx2yþdymentioning
confidence: 99%
See 2 more Smart Citations
“…[32] Several authors noted that q 5 1 is a critical value in the Monte-Carlo simulation of hillslopes or catchments [Saghafian et al, 1995;Nahar et al, 2004;Morbidelli et al, 2006;Jones et al, 2009]. The case of a periodic variation of infiltrability best illustrates the transition at q 5 1.…”
Section: Fðyþgðx2yþdymentioning
confidence: 99%
“…Vegetation, topography, and soil surface properties (natural or anthropogenic) are recognized to be important sources of variability [Dunne et al, 1991]. Runon, which reduces the total runoff volume and sediment yield, is a hydrological process which must be taken into account in models [Saghafian et al, 1995;Woolhiser et al, 1996;Howes and Abrahams, 2003;Adams et al, 2012]. Because of runon, the runoff volume at the stream is less than the sum of the volumes produced by each pixel of the hillslope or catchment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These basic factors hold when one extends the analysis to infiltration in locally nonuniform soil profiles or spatially varying systems at the scale of the field or the watershed. A large body of research has shown that spatial variability of soil properties affect infiltration at such scale [Russo and Bresler, 1982;Sivapalan and Wood, 1986;Saghafian et al, 1995]. The effect of local heterogeneity within the soil profile on infiltration was also demonstrated for layered or nonuniform soils, mainly relying on the Green and Ampt [1911] approach [Childs and Bybordi, 1969;Beven, 1984;Selker et al, 1999;Chu and Marino, 2005].…”
Section: Introductionmentioning
confidence: 99%
“…However, the efficacy of such water harvesting systems depends on the accuracy of the predicted hydrological response of the water catchments to the local rainfall. Spatial and temporal variability of soil and rainfall properties influence the infiltration process, and consequently, the generation of surface flow [Singh, 1997;Saghafian et al, 1995]. These variables dominate also the process of the soil surface sealing [Assouline, 2004].…”
Section: Introductionmentioning
confidence: 99%